Comparison of hemagglutinating pili of Haemophilus influenzae type b with similar structures of nontypeable H. influenzae. - Gilsdorf, J R (1992)
Thirty-eight clinical isolates of nontypeable Haemophilus influenzae were tested for the presence of hemagglutinating pili similar to those of H. influenzae type b (Hib) that mediate buccal epithelial cell adherence. Four endogenously hemagglutinating (HA+) strains were identified, and eight additional HA+ variants were obtained from HA- strains by erythrocyte enrichment. All 12 HA+ nontypeable H. influenzae isolates bound antisera directed against denatured pilins of Hib, but none bound antisera against assembled native pili of Hib. In erythrocyte- and buccal-cell-binding assays, HA+ nontypeable H. influenzae binding was reduced compared with HA+ Hib binding and was not significantly different from HA- nontypeable H. influenzae binding. Both HA- and HA+ nontypeable H. influenzae binding was increased over binding of HA- Hib. HA+ nontypeable H. influenzae strains agglutinated adult erythrocytes that possess the Anton antigen, which is thought to be the receptor for Hib pili, and did not agglutinate cord or Lu(a-b-) dominant erythrocytes, which lack the Anton antigen. Electron microscopy of HA- and HA+ variants of three nontypeable H. influenzae strains showed few or no surface appendages on the HA- organisms, but piluslike structures were seen on many organisms from two HA+ nontypeable H. influenzae strains and on a few organisms from one strain. Thus, nontypeable H. influenzae appears to possess structures that are immunologically similar to the pilins that make up the hemagglutinating pili of Hib. However, nontypeable H. influenzae appears to also possess mechanisms for erythrocyte and buccal cell adherence that are not directly correlated with the presence of a hemagglutinating pilus.